2010
DOI: 10.1017/s0954579410000295
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, social competence, and academic achievement in Chinese children: A 5-year longitudinal study

Abstract: The primary purpose of this longitudinal study was to examine, in a sample of Chinese children (initial M age = 8 years, N = 1,140), contributions of aggression to the development of social competence and academic achievement. Five waves of panel data on aggression and social and school performance were collected from peer evaluations, teacher ratings, and school records in Grades 2 to 5. Structural equation modeling revealed that aggression had unique effects on later social competence and academic achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
3
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 46 publications
8
107
3
15
Order By: Relevance
“…This study was looking at two factors of social integration in Tinto's SIM and has introduced the Student Online Learning Readiness (SOLR) conceptual model with the purpose of extending Tinto's social integration to an online learning environment. The significant influences of social competencies (Chen et al, 2010;Parker et al, 2006;Williams, 2003), communication competencies (Betermieux & Heuel, 2009;Dabbagh, 2007;Dabbagh & Bannan-Ritland, 2005;Volery & Lord, 2000;Williams, 2003), and technical competencies (Osika & Sharp, 2002;Selim, 2007;Watulak, 2012;Whale, 2006) have been verified by previous research. Therefore, it is now found to be possible to measure the levels of learners' social, communication, and technical competencies through use of the Student Online Learning Readiness (SOLR) instrument before the learners take an online course.…”
Section: Final Four-factor Structuresupporting
confidence: 57%
See 2 more Smart Citations
“…This study was looking at two factors of social integration in Tinto's SIM and has introduced the Student Online Learning Readiness (SOLR) conceptual model with the purpose of extending Tinto's social integration to an online learning environment. The significant influences of social competencies (Chen et al, 2010;Parker et al, 2006;Williams, 2003), communication competencies (Betermieux & Heuel, 2009;Dabbagh, 2007;Dabbagh & Bannan-Ritland, 2005;Volery & Lord, 2000;Williams, 2003), and technical competencies (Osika & Sharp, 2002;Selim, 2007;Watulak, 2012;Whale, 2006) have been verified by previous research. Therefore, it is now found to be possible to measure the levels of learners' social, communication, and technical competencies through use of the Student Online Learning Readiness (SOLR) instrument before the learners take an online course.…”
Section: Final Four-factor Structuresupporting
confidence: 57%
“…Gabriel et al (2009) described social competencies as the ability "to continually develop and share ideas, promote their own position against contrary opinions and compromise despite linguistic and cultural barriers" (p. 1251). Even though researchers have used different terms to refer to social competencies, in many studies researchers have concluded that positive relationships between social competencies and academic achievement do exist (Anderson & Messick, 1974;Chen et al, 2010;Dalley, Bolocofsky, & Karlin, 1994;Tan et al, 2010).…”
Section: Social Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorly regulated disruptive children are also more likely to undermine group functioning, experience social rejection, and develop poor academic motivation (Ladd, Birch & Buhs, 1999;Chen, Huang, Chang, Wang & Li, 2010;Vitaro, Brendgen, Larose & Tremblay, 2005). By contrast, the cognitive control skills that underlie children's ability to remain engaged in the classroom are likely to contribute to positive psychosocial adjustment.…”
Section: Academic Performance: Is Achievement All That Matters?mentioning
confidence: 99%
“…Estudos recentes têm demonstrado que a predição não segue um modelo causal, mas antes um modelo de influências transacionais, definidas como relações longitudinais intrapessoais recíprocas entre domínios do funcionamento adaptativo (Bornstein et al, 2010). Trajetórias de desenvolvimento com influências entre domínios foram identificadas para habilidades sociais e desempenho acadêmico (Chen et al, 2010), habilidades sociais e problemas de comportamento (Burt & Roisman, 2010;Van Lier & Koot, 2010), desempenho e problemas de comportamento (Moilanen, Shaw, & Maxwell, 2010).…”
unclassified